2022
DOI: 10.3389/fmats.2021.733358
|View full text |Cite
|
Sign up to set email alerts
|

A Review of UltraHigh Frequency Ultrasonic Transducers

Abstract: The ultrahigh-frequency (UHF) ultrasonic transducers are active in various fields, including nondestructive evaluation in the semiconductor industry, microscopic biological organization imaging in biomedicine, particle manipulation, and so on. In these fields ultrahigh-frequency (UHF) ultrasonic transducers play a critical role in the performance of related equipment. This article will focus on the topic of ultrahigh-frequency ultrasonic transducers’ preparation, and reviews three aspects: material selection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 77 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Table 4 exhibits the results of the substrate examinations. Epoxy resins are commonly utilized as a substrate for the matching layers of ultrasonic transducers due to their cost-effectiveness [27], with a hardness up to Shore D70 or even higher. However, they have a higher acoustic impedance and acoustic attenuation.…”
Section: Results Of Substrate Testingmentioning
confidence: 99%
“…Table 4 exhibits the results of the substrate examinations. Epoxy resins are commonly utilized as a substrate for the matching layers of ultrasonic transducers due to their cost-effectiveness [27], with a hardness up to Shore D70 or even higher. However, they have a higher acoustic impedance and acoustic attenuation.…”
Section: Results Of Substrate Testingmentioning
confidence: 99%
“…This is because the exposure time needs to be increased to remove higher cells with low ultrasound frequency. Increasing the exposure time will be caused the increase in power input that leads to higher electrical power consumption and will affect the electrical cost increase (Chen et al, 2022). So this lowest frequency is not economical for harmful algae removal.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that ultrasound has a detrimental effect on organism structural and functional status, and hence, sonication is applied to reduce cyanobacterial blooms in eutrophic water (Phull et al, 1997;Lee et al, 2010). Research has found that sonication inhibits the growth rate of cyanobacteria by causing the rupture or collapse of gas vesicles due to cavitational effects, membrane disruption, damage to photosynthetic activity, and inhibition of cell division and cell cycle; the extent of the damage and thus bloom control is dependent on parameters such as ultrasonic frequency, power intensity, and exposure duration (Chen et al, 2022). Although it may lead to the release of toxins due to cyanobacterial cell lysis (Song et al, 2005 ;Purcell et al, 2013 ), sonication has also been reported to be effective in degrading the cyanotoxins (Song et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some work, the focused lenses were added to achieve focused imaging without a destructive pressing effect on the piezoelectric element. [ 177 ] However, the lower sensitivity due to attenuative losses and the mechanical quality of the lens limited its practical application. [ 178 ] In recent studies, with the development of novel piezoelectric materials and composites, planar single‐element transducers have always been fabricated and characterized using standard methods to check the performance of new materials because of their simplest configuration.…”
Section: Piezoelectric Materials and Ultrasound Transducersmentioning
confidence: 99%